Guerra y cultura: transformaciones y discursividades sobre la vida cultural samaria durante la guerra de los mil días - Laura Carbonó-López; David Zea-Lopera (Eleuthera)
This article analyzes the impact of the Guerra de los Mil Dias (Thousand Days War) on the cultural transformations faced by the Department of Magdalena, particularly the city of Santa Marta. The work was carried out in the light of some studies and press documentation that rest in the Archivo General de la Nación (General Archive of the Nation), Archivo Histórico del Magdalena (Historical Archive of Magdalena) and the newspaper and periodicals archive at Universidad de Antioquia, that allowed to understand, to a certain extent, how they developed within the framework of said conflict. For this reason, a state of the art study was carried out which highlighted the attempts to address cultural changes in the region, by emphasizing festivities, education, and music as a central part of the search for an identity in line with current political models. This was restrained by the economic ups and downs experienced by the population due to its status as a transit city.